A NOVEL APPROACH FOR THE FABRICATION AND ANALYSIS OF 3D PRINTING FILAMENT MATERIALS - POTNURU SUMANTH; MATTA PRADEEP; PAPPU PAVAN KUMAR; MUDILI DILLESWARI; KOMARAM YUVARAJU; KONDETI VEDHAGAYATRI; Dr. M. SRINIVASA RAO (The Bioscan, 2025)
AM technologies have rapidly evolved, and the most popular method for polymer-based 3D printing applications is FDM. The ability to tailor mechanical properties through both material selection and, importantly, process settings such as infill geometry has created new opportunities for sophisticated engineering applications. This research paper aims to investigate the effect of changes in the internal infill pattern geometry on the mechanical properties of normal and hybrid composite filaments fabricated through FDM. The presented study makes use of four normal materials, namely (PLA) Polylactic Acid, (ABS) Acrylonitrile Butadiene Styrene, Nylon, (PETG) Polyethylene Terephthalate Glycol and two different commercially available hybrid material combinations, namely PLA-Copper and PLA-Bronze. For all materials, samples were fabricated with a fixed 60% infill density while the internal infill pattern geometry was systematically varied. Standardized mechanical tests were performed to determine performance attributes and structural integrity for each material-pattern combination. The testing included tensile, compressive, impact, and shear tests. A statistical analysis was done on the resulting experimental data. Thereafter, this work offers an essential and new understanding of how the infill pattern influences the structural performance for certain hybrid materials used in high-performance additive manufacturing applications and thus provides recommendations for refined design strategies. KEYWORDS: FDM, Additive Manufacturing, 3D Printing, Polymer, Hybrid Composite Filaments, Infill Pattern Geometry, Mechanical Properties, PLA, ABS, Nylon, PETG, PLA-Copper, PLA-Bronze, Infill Density, Tensile, Compressive, Impact, Shear Tests, Structural Performance, Statistical Analysis.